The Role of Education Management in Improving the Quality of Excellent School Education - Mona Novita; Muhammad Solihin (INNOVATIO: Journal for Religious Innovation Studies, 2020)
One of the main themes in discussing excellent schools is regarding "the process of making the students to excellent" and quality assurance managemnet of excellent schools. This paper examines the nature of superior schools and quality assurance management of superior schools, which consists of: (1) a harmonious school atmospehre, (2) management based on supervision (control management), (3) determination to improvesustainable quality, (4) the school work reference is productivity (efficient and effective), and (5) tough leadership. Excellent schools are another version of excellent students. In this point, the "student enhancement process" becomes the main goal in achieving quality output. This follows a "System Theory" in Excellent Schools expressed by J. Alan Thomas that negative / bad input, if the enhancement process + (positive), it will result in almost + (excellent) output. The process of enhancement input in superior schools is: (1) the ability of professional teachers consisting of professional competence, competence in learning, mentoring, communication with students and in evaluating, (2) the curriculum uses a differentiation curriculum and links subject matter with modern inventions in accordance with current technological developments, (3) extracurricular programs and (4) collaborative networks with educational institutions. Salah satu tema utama dalam pembahasan tentang sekolah unggulan adalah mengenai “proses pengunggulan siswa” dan manajemen penjaminan mutu sekolah unggulan. Makalah ini mengkaji tentang hakikat sekolah unggulan dan manajemen penjaminan mutu sekolah unggulan yang terdiri dari: (1) iklim sekolah yang harmonis, (2) manajemen yang berbasis pengawasan (control management), (3) tekad untuk meningkatkan mutu secara terus menerus (sustainability), (4) acuan kerja sekolah adalah produktivitas (efficient dan effektive), dan (5) kepemimpinan yang kuat (leadership). Sekolah unggulan merupakan versi lain dari pengunggulan siswa. Disini, “proses pengunggulan siswa” itu yang menjadi sasaran utama dalam mencapai output yang berkualitas. Hal ini mengikuti sebuah “Teori Sistem” dalam Sekolah Unggulan yang diungkapkan oleh J. Alan Thomas bahwa input yang negatif/ buruk, apabila Proses pengunggulannya + (positif) maka akan menghasilkan output yang cencerung + (Unggul). Adapun proses pengunggulan input dalam sekolah unggulan adalah: (1) kemampuan guru yang profesional yang terdiri dari kompetensi profesional, kompetensi dalam pembelajaran, pembimbingan, komunikasi dengan peserta didik dan dalam mengevaluasi, (2) kurikulum menggunakan kurikulum diferensiasi dan mengkaitkan materi-materi pelajaran dengan penemuan modern sesuai dengan perkembangan teknologi saat ini, (3) program ekstrakurikuler dan (4) jaringan kerjasama dengan pihak lembaga pendidikan.